Peran Komunikasi dalam suatu Organisasi The Role of Communication in an Organization - Ariel Angelo Nanlohy; Chontina Siahaan (CV. ITTC INDONESIA, 2021)
This research study aims to create students who understand the deepest meaning of communication, and train human sensitivity to the relationship between communication and organization. Communication is a habit of every human being. Every human being certainly communicates with other humans every day. Communication is an activity of delivering a message that has the aim of understanding the perception between the communicator to the communicant. This research is based on qualitative research and researched individually. In the business process in mobilizing the potential and ability in the organization, it is certainly based on various human aspects. This certainly motivates members to study various psychological motives. In addition to this, there is a need and from there a concern is born that triggers members to realize the desired behavior of the organization itself. The results of this study are: (1) Communication is an activity to convey the essence of an entity or from one collection to another, which is passed by the use of instructions, characteristics, and various forms of code whose purpose is to be accepted and understand each other. (2) The organization is a unit that becomes a forum and a means in the vision to achieve several goals. The goals in the organization are based on various components, namely there are many people, work relations, work specialists and rational awareness of members according to their respective abilities and specializations.